2017
DOI: 10.3389/fnmol.2017.00393
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin Derivative 7-Bromoindirubin-3-Oxime (7Bio) Attenuates Aβ Oligomer-Induced Cognitive Impairments in Mice

Abstract: Indirubins are natural occurring alkaloids extracted from indigo dye-containing plants. Indirubins could inhibit various kinases, and might be used to treat chronic myelocytic leukemia, cancer and neurodegenerative disorders. 7-bromoindirubin-3-oxime (7Bio), an indirubin derivative derived from indirubin-3-oxime, possesses inhibitory effects against cyclin-dependent kinase-5 (CDK5) and glycogen synthase kinase-3β (GSK3β), two pharmacological targets of Alzheimer's disease (AD). In this study, we have discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Like most diseases, PD is modulated by various environmental and genetic factors. Genetic mutations including the mutation in A53T Synuclein [ 3 ] and environmental factors such as sedentary lifestyle, exposure to certain insecticides, neurotoxins, MPTP, 6-OHDA, rotenone and paraquat might induce PD [ 2 , 4 ]. MPTP is a lipid soluble substance, able to cross the blood-brain barrier, oxidized by the glial enzyme Monoamine oxidase B to a toxic agent called 1-methyl-4-phenylpyridinium-4-methyl-1 (MPP + ) [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…Like most diseases, PD is modulated by various environmental and genetic factors. Genetic mutations including the mutation in A53T Synuclein [ 3 ] and environmental factors such as sedentary lifestyle, exposure to certain insecticides, neurotoxins, MPTP, 6-OHDA, rotenone and paraquat might induce PD [ 2 , 4 ]. MPTP is a lipid soluble substance, able to cross the blood-brain barrier, oxidized by the glial enzyme Monoamine oxidase B to a toxic agent called 1-methyl-4-phenylpyridinium-4-methyl-1 (MPP + ) [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…Aβ oligomer preparation was described in previous studies reported by us [27][28][29]. Brie y, Aβ peptide was dissolved in hexa uoroisopropanol (HFIP, Aladdin, Shanghai, China) to form Aβ monomers.…”
Section: Preparation Of Aβ Oligomersmentioning
confidence: 99%
“…. The NORT were conducted in an open-field arena (30 × 30 × 30 cm) constructed with polyvinyl chloride, plywood, and acrylic as previously described [26]. The tasks included a training session and a recognition session for two consecutive days.…”
Section: Novel Object Recognition Test (Nort)mentioning
confidence: 99%